European radiographers’ challenges in mammography education and clinical practice - Meystre, Nicole Richli (2017)
Purpose: Although guidelines have been produced, there is variability within European countries regarding mammography imaging practice and staff training. The aim of this study was to systematically synthesize available evidence on European radiographers’ challenges in clinical education and practice concerning mammography. Conclusion: The need for training has been highlighted in this review for a multi-professional approach for breast cancer detection. Challenges in education/training and in clinical practice were observed reviling room for improvements in both areas.